Hollow-Structured Carbon-Coated CoxNiySe2 Assembled with Ultrasmall Nanoparticles for Enhanced Sodium-Ion Battery Performance - Chao Wang; Weijie Si; Xiongwu Kang (Inorganics)
Transition metal selenides are considered one of the most promising materials for sodium-ion battery anodes due to their excellent theoretical capacity. However, it remains challenging to suppress the volume variation and the resulted capacity decay during the charge–discharge process. Herein, hollow-structured CoNiSe2 dual transition metal selenides wrapped in a carbon shell (HS-CoxNiySe2@C) were deliberately designed and prepared through sequential coating of polyacrylonitrile (PAN), ion exchange of ZIF-67 with Ni2+ metal ions, and carbonization/selenization. The hollow structure was evidenced by transmission electron microscopy, and the crystalline structure was confirmed by X-ray diffraction. The ample internal space of HS-CoxNiySe2@C effectively accommodated volume expansion during the charge and discharge processes, and the large surface area enabled sufficient contact between the electrode and electrolyte and shortened the diffusion path of sodium ions for a feasible electrochemical reaction. The surface area and ionic conductivity of HS-CoxNiySe2@C were strongly dependent on the ratio of Co to Ni. The synergistic effect between Co and Ni enhanced the conductivity and electron mobility of HS-CoxNiySe2@C, thereby improving charge transfer efficiency. By taking into account the structural advantages and rational metal selenide ratios, significant improvements can be achieved in the cycling performance, rate performance, and overall electrochemical stability of sodium-ion batteries. The optimized HS-CoxNiySe2@C demonstrated excellent performance, and the reversible capacity remained at 334 mAh g−1 after 1000 cycles at a high current of 5.0 A g−1.